Management of a primary retroperitoneal hydatid cyst ruptured in the abdominal wall: A case report. (2020) - Maghrebi, Houcine; Ben Mahmoud, Ahmed; Haddad, Anis; Cheikhrouhou, Sarra; Sebei, Amine; Chaker, Youssef; Boukriba, Seif; Jeribi, Bedis; Rebai, Wael; Kacem, Montasser Jameleddine
Highlights: Hydatid disease is endemic in North Africa countries such as Tunisia. Retroperitoneal location is scarce. Parietal complications are rarely described even in endemic geographic locations. Management of parietal complications of hydatid cysts is not consensual. Surgical drainage remains the gold standard. Abstract: Introduction: Hydatid disease is a global zoonosis. Any organ of the human body can be involved. Single or multiple locations are reported. However, retroperitoneal hydatid cysts are uncommon. Furthermore, parietal complications are rarely reported in literature. Therefore, the management of hydatid cysts ruptured in the abdominal wall remains challenging. Presentation of case: In this case report, we aim to describe our experience in treating a primary retroperitoneal hydatid cyst with rupture into abdominal wall in an 87-year-old woman who presented with a 15-centimeter mass of the right flank. Hydatid serology test was positive. An abdominal CT scan showed a 20-centimeter cystic mass of retroperitoneum extended to the abdominal wall with several septa within and enhanced thick wall. The patient underwent a surgical elective drainage with perioperative antiparasitic chemotherapy. Follow-up showed no recurrence. Discussion: Primary retroperitoneal hydatid cyst with parietal complications is scarce and barely described in literature. We performed a review of the recent relevant literature that deals with this subject. None of the hydatid cysts reported in 55 cases was located in retroperitoneum. The top seven countries of origin are located in Mediterranean region except for India. Imaging is compulsory for the diagnosis along with patient's history, physical examination and hydatid serology. The treatment is surgical and must be must be covered by antiparasitic chemotherapy. Conclusion: Primary retroperitoneal hydatid cyst extended to the abdominal wall remains a rare and challenging diagnosis that must be considered in endemic countries.